Knowledge of Medical Students About Obstetric Fistula in Pakistan - Still A Tragedy (Medical Forum Monthly, 2024)
Objective: To assess the knowledge of medical students about obstetric fistula in Pakistan—still a tragedy.Study design: Cross sectional study. Place and Duration of Study: This study was conducted at Hamdard University Hospital, Karachi from 01.01.2014 to 15.03.2014.Materials and Methods: A cross sectional study of knowledge of medical students of Final Year MBBS was conducted using a pretested self-administered questionnaire. Total 100 questionnaires were filled out of which, 87 were filled by medical students and 13 by house officers. The data was evaluated and analysed on SPSS.Results: The results shows that the overall knowledge of our students and junior doctors regarding obstetric fistula was below average. They are not well aware of the substantial burden of obstetric fistula in our community, its root causes and preventive measures to be taken. This shows the need to giving more weightage to this topic in curriculum and re-structuring their training program.Conclusion: The presence of trained professional is crucial for the early detection and timely management of such complications. To achieve this within limited resources these students and young doctors are an important cadre of health professionals, therefore the curriculum should lay emphasis on community based clinically oriented teaching.